Analisis Kepemimpinan Transformasional dan Teori U dalam Fourth Industrial Revolution (4IR) yang Menumbuhkan Inovasi di Sekolah Kristen [Analysis of Transformational Leadership and U Theory in Fourth Industrial Revolution (4IR) That Grows Innovation in Christian Schools] - Hermawati, Oki; Richard, Richard (Universitas Pelita Harapan, 2022)
Transformational leadership and the emergence of the U theory and the Fourth Industrial Revolution 4IR is an interesting topic to be discussed in the field of education. This paper is intended to discuss the above topic in the context of Christian education, specifically in Christian schools. The directors and heads in Christian schools are called to develop their students' competency. This in turn, leads to innovations that create new breakthroughs in the field of education that is constantly changing throughout time. Utilizing the U theory to trace the roots of the problem allows the heads of Christian schools to have an open mind, an open heart, and an open will which in turn prepares them to develop their Christian schools continually.BAHASA INDONESIA ABSTRACTKepemimpinan transformasional dan kehadiran Teori U serta konteks Fourth Industrial Revolution (4IR) merupakan rangkaian menarik untuk dikaji dan dibahas dalam konteks dunia pendidikan. Pembahasan yang dilakukan dalam tulisan ini memiliki tujuan untuk melihat rangkaian di atas dalam konteks pendidikan Kristen terutama sekolah Kristen. Para pemimpin dari sekolah Kristen memiliki panggilan untuk melakukan transformasi di dalam organisasinya dan mengembangkan kompetensi dari para pendidik sehingga menumbuhkan inovasi nyata yang menghasilkan terobosan-terobosan baru dan karya dalam dunia pendidikan dalam konteks zaman yang terus berubah. Upaya transformasi dari sekolah Kristen dengan merunut akar permasalahan dengan menggunakan Teori U memampukan pemimpin untuk membuka pikiran (open mind), membuka hati (open heart) dan membuka keinginan (open will) sehingga memiliki kesiapan untuk terus memajukan sekolah Kristen yang dipimpinnya dan selaras dengan visi dan misi dari sekolah Kristen itu sendiri.